2019
DOI: 10.1111/his.13962
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing and RNA sequencing analyses of acinic cell carcinomas of the breast

Abstract: Aims Acinic cell carcinoma (ACC) of the breast is a rare histological form of triple‐negative breast cancer (TNBC). Despite its unique histology, targeted sequencing analysis has failed to identify recurrent genetic alterations other than those found in common forms of TNBC. Here we subjected three breast ACCs to whole‐exome and RNA sequencing to determine whether they would harbour a pathognomonic genetic alteration. Methods and results DNA and RNA samples from three breast ACCs were subjected to whole‐exome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…No pathognomonic genetic alterations have been identified in three breast ACCs analysed by whole-exome sequencing. The alterations identified were similar to those seen in conventional TNBC of NST [ 39 ]. On the basis of the small series analysed, commonly occurring mutations affect the following genes: PIK3CA, KMT2D, ERBB4/ERBB3, NEB, BRCA1, MTOR, CTNNB1, INPP4B and FGFR2 [ 11 , 34 , 40 ].…”
Section: Acinic Cell Carcinoma (Acc) Of the Breastsupporting
confidence: 63%
“…No pathognomonic genetic alterations have been identified in three breast ACCs analysed by whole-exome sequencing. The alterations identified were similar to those seen in conventional TNBC of NST [ 39 ]. On the basis of the small series analysed, commonly occurring mutations affect the following genes: PIK3CA, KMT2D, ERBB4/ERBB3, NEB, BRCA1, MTOR, CTNNB1, INPP4B and FGFR2 [ 11 , 34 , 40 ].…”
Section: Acinic Cell Carcinoma (Acc) Of the Breastsupporting
confidence: 63%
“…Salivary gland acinic cell carcinomas are characterized by the t(4;9)(q13; q31) translocation, which results in a rearrangement involving the nuclear transcription factor NR4A3 (ref. 15 ), whereas breast acinic cell carcinomas seem not to harbor a pathognomonic genetic alteration and consistently display complex genomes and TP53 mutations 16,17 . Here we sought to determine whether breast PAs and MECs arising in the breast would be underpinned by fusion genes, in particular those reported in their salivary gland counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the presence of the poorly differentiated component plays an important role during the disease progression. Recent research had showed that the tumors had somatic genetic alterations similar to those of common forms of TNBC and may display HR deficiency or microsatellite instability, without any pathognomonic genetic alterations 20 . These findings provide further insights to understand why AcCCs may evolve into or parallel to high‐grade TNBC 20 …”
Section: Discussionmentioning
confidence: 86%